An efficient model for the dynamic vehicle-track-bridge-soil interaction system. (15th February 2022) - König, Paul; Salcher, Patrick; Adam, Christoph
Abstract: A semi-analytical approach based on a lumped parameter model is presented for the analysis of the dynamic interaction system of train, track, bridge, and subsoil. Herein, the bridge and the track are modeled as Euler–Bernoulli beams, which are connected through the viscoelastic track bed. The viscoelastic supports of the bridge model capture the flexibility and damping of the subsoil below the foundations. Complex modal expansion of the deformation approximates the response of the non-classically damped bridge-soil subsystem, while a Rayleigh–Ritz approximation is used to efficiently describe the track deflection. To achieve the coupling of the mechanical equations of these subsystems, a variant of component mode synthesis (CMS) is applied. The mass–spring–damper (MSD) system representing the moving train is coupled to the resulting system of equations for the track-bridge-soil subsystem by a discrete substructuring technique (DST). Geometric track irregularities describing the deviation of the track from perfectly straight and smooth are accounted for by random irregularity profile functions. The results of the proposed model are compared with a finite element model to validate the modeling approach. In an application example, the effects of track irregularities and the influence of the track on the dynamic response of a bridge are discussed. The comparison of results with and without soil–structure interaction of the bridge outlines the great influence of the subsoil properties on the dynamic response in case of resonance. Highlights: Efficient prediction of the interaction between vehicle, track, bridge, and soil. Component mode synthesis with a localized Rayleigh–Ritz approximation of the track. Novel findings on soil–structure interaction with track irregularities.